Examining political participation in Lithuania: The direct and mediated effects of social trust - Gaidytė, Teodora; Muis, Jasper (Baltic Journal of Political Science, 2021)
This article investigates the effects of social trust, both direct and mediated – via internal and external efficacy – on different forms of political participation in post-communist Lithuania. The relationship between social trust and participation features prominently in the social capital and civic culture literature, but little empirical evidence exists that supports it, especially in post-communist democracies. We use the Lithuanian National Elections Study 2012 to test our hypotheses and replicate our analysis with the European Social Survey waves of 2014 and 2016. Our results show that social trust increases turnout, because it is related to a sense of external efficacy, which in turn enhances the likelihood that people vote. There is, however, no association between social trust and being involved in other institutionalised politics, namely, working for a political party. Interestingly, we find a positive indirect effect for non-institutionalised political participation: social trust increases external efficacy, which in turn enhances protest behaviour. Overall, however, social trust does not lead to more protesting, because the former is at the same time positively related to political trust, which seems to decrease, rather than increase non-institutionalised participation. In sum, our findings demonstrate that explanations for political participation based on the core element of social capital – social trust – work out differently for different forms of political participation.